Фомка - белый медвежонок: рассказы / В. В. Чаплина - Чаплина Вера Васильевна (Репро, 2014)
Экземпляры: БС (20170211) / Инвентарный номер: РТШ53820 / Сис.шифр: Р2 / Авт.знак: Ч-19 / ГРНТИ: 17.82.93 / ББК: 84(2)